Entitativity and implicit measures of social cognition. (20th May 2021) - Phillips, Ben
Abstract : I argue that in addressing worries about the validity and reliability of implicit measures of social cognition, theorists should draw on research concerning "entitativity perception." In brief, an aggregate of people is perceived as highly "entitative" when its members exhibit a certain sort of unity. For example, think of the difference between the aggregate of people waiting in line at a bank versus a tight‐knit group of friends: The latter seems more "groupy" than the former. I start by arguing that entitativity perception modulates the activation of implicit biases and stereotypes. I then argue that recognizing this modulatory role will help researchers to address concerns surrounding the validity and reliability of implicit measures.